Reduced empathic concern leads to utilitarian moral judgments in trait alexithymia - Patil, Indrajeet; Silani, Giorgia (Frontiers in Psychology, 2014)
Recent research with moral dilemmas supports dual-process model of moral decision making. This model posits two different paths via which people can endorse utilitarian solution that requires personally harming someone in order to achieve the greater good (e.g., killing one to save five people): (i) weakened emotional aversion to the prospect of harming someone due to reduced empathic concern for the victim; (ii) enhanced cognition which supports cost-benefit analysis and countervails the prepotent emotional aversion to harm. Direct prediction of this model would be that personality traits associated with reduced empathy would show higher propensity to endorse utilitarian solutions. As per this prediction, we found that trait alexithymia, which is well-known to have deficits in empathy, was indeed associated with increased utilitarian tendencies on emotionally aversive personal moral dilemmas and this was due to reduced empathic concern for the victim. Results underscore the importance of empathy for moral judgments in harm/care domain of morality.